2014
DOI: 10.1007/s10064-014-0665-x
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental investigation of hydraulic fracture propagation in fractured blocks

Abstract: Natural fractures in reservoirs can be the cause of many adverse effects during hydraulic fracturing treatment. In the present paper, hydraulic fracturing tests are used to investigate the interaction of a propagating hydraulic fracture with a natural fracture in the fractured blocks. Systematic experiments were designed and performed on the cement blocks with different pre-existing fracture strikes and dips (30°, 60°and 90°). The effect of horizontal stress difference on the propagation of hydraulic fractures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Experimentally, several researchers [3][4][5][6][7][8][9][10][11][12][13] have widely investigated the problem of hydraulic and natural fractures interaction to improve the success rate and fracturing effect. On the basis of experimental studies, it is conceivable that several events may occur during the period of hydraulic fracture propagation towards the natural fracture and beyond.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, several researchers [3][4][5][6][7][8][9][10][11][12][13] have widely investigated the problem of hydraulic and natural fractures interaction to improve the success rate and fracturing effect. On the basis of experimental studies, it is conceivable that several events may occur during the period of hydraulic fracture propagation towards the natural fracture and beyond.…”
Section: Introductionmentioning
confidence: 99%
“…Following the previous experimental works, Warpinski and Teufel (1987), Warpinski (1991), Zhou et al (2008) and Dehghan et al (2014Dehghan et al ( , 2015 conducted many hydraulic fracturing experiments to investigate induced fracture propagation behaviour and fracture geometry in naturally fractured reservoirs. They observed three types of interactions between hydraulic and natural fractures which were crossing, arrest by opening and dilating the natural fracture, and arrest by shear slippage of the natural fracture with no dilation and fluid flow along the natural fracture.…”
Section: Introductionmentioning
confidence: 99%
“…According to tensile strength criterion, hydraulic fractures on the wellbore wall initiate when the principal tensile stress within the rock (due to the fluid pressure within the rock) exceeds the minimum principal stress plus the tensile strength of the rock (Haimson, 1967;Hossain, Rahman, & Rahman, 1967, 2000Hubbert & Willis, 1957). A series of lab experimental studies have been conducted in the past to investigate the influence of natural fracture on the fracture initiation and propagation under different reservoir conditions (Beugelsdijk, De Pater, & Sato, 2000;Blanton, 1986;Dehghan, Goshtasbi, Ahangari, & Jin, 2014Gu et al, 2012;Olson, Bahorich, & Holder, 2012;Suarez-Rivera, Burghardt, Stanchits, Edelman, & Surdi, 2013;Tie, Wei, & Xueliang, 2011;Warpinski & Teufel, 1987;Zhou, Chen, Jin, & Zhang, 2008;Zhou, Jin, & Chen, 2010). Some experimental investigations (Blanton, 1982;Daneshy, 1974;Lamont & Jessen, 1963) have demonstrated that the advancing induced hydraulic fracture crosses the natural fracture without any significant change in its direction, turns into the natural fracture and dilates it or, in some cases, turns into the natural fracture and beside the dilation of natural fracture, breaks out again by a fracture or flaw along the natural fracture.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, laboratory experiments have been used to study hydraulic fracturing using freshwater as a fracturing fluid [3,[16][17][18][19][20][21][22]. Various studies [23][24][25][26][27][28][29] investigated important factors (such as rock structure, in situ stress, viscosity, and the injection rate of a fracturing fluid) that affect the hydraulic fracturing process.…”
Section: Introductionmentioning
confidence: 99%